TINJAUAN PENGGUNAAN BERKAS REKAM MEDIS DENGAN KONSEP FAMILY FOLDER GUNA MENUNJANG KUALITAS PELAYANAN DI PUSKESMAS CIBODAS - Luqman Nul Hakim; Encep Hada; Ayu Hendrati Rahayu; Rizqy Dimas Monica (UPPM Politeknik TEDC Bandung, 2019)
Based on preliminary studies conducted from February 3, 2019 to February 8, 2019, with the use of the family folder medical record file, there is still a lack of service. There were 30 families who were treated in two poles together. Then a sample of 30 patients was taken with a presentation (100%). This results in other family members having to wait for other family members to be checked with an average of 40 minutes 02 seconds. Where patients should not be left waiting for a long time to get services because the services provided must be immediately carried out. The purpose of this study was to determine the use of family folder medical record file at the Cibodas Health Center. The research method used is descriptive method with quantitative and qualitative approaches. Data collection techniques are by observation, interview, questionnaire and literature study. The research instrument used a research table, interview guidelines, questionnaire, stopwatch, stationery and calculator. The results of the examination waiting time became longer because of the added examination time in the first poly with an average time of 32 minutes 10 seconds and not yet available SOPs for the service of two family members in an simultaneously using the family folder medical record file. Advice that can be given is to immediately make an SOP for examination of two patients together in one family, pay more attention to waiting time and use of the family folder medical record file for the future so that patient satisfaction is met as a whole and monitor also periodic evaluations for the better filing of medical records.